Using Self-Assessment to Help Young Learners Improve their Speaking: Research Report - Loor Lizarzaburu, Silvia Alexandra (2024)
The purpose of this study was to help young learners to decrease the stress level that made them feel discouraged, and lack of confidence when participating in speaking activities; finding the tools and aids that guided them to increase their speaking skills and provide them the courage to be able to use them in a class context. Once the results were shown in this study, it can be concluded that the participants increased their confidence when speaking.